CARROT (DAUCUS CAROTA L.) AND TOMATOES (SOLANUM LYCOPERSICUM) PUDDING TO LOWER THE BLOOD PRESSURE OF THE ELDERLY - Retno Wahyuningsih; Olga Fuji Anugrah; Ni Ketut Sri Sulendri; Suhaema Suhaema; Made Darawati (Journal of Social Research, 2022)
Background: Hypertension in the elderly is still a health problem that needs to be taken seriously. One of the non-pharmacological treatments for hypertension is to utilize the potassium content in fruits, vegetables and tubers such as carrots and tomatoes which contain high antioxidants such as potassium, lycopene, vitamins A, B, and C. Objective: To determine the effect of giving carrot (Daucus Carota L.) and tomato (Solanum Lycopersicum) pudding on reducing blood pressure in the elderly. Methods: This study used a Quasy-Experiment type with a Pretest-Posttest With Control Group research design. The number of samples in this study amounted to 22 people and selected by Simple Random Sampling. The sample was divided into 2 groups, namely the control group and the intervention group by giving carrot and tomato pudding for 7 consecutive days. Results: Statistical tests stated that the systolic blood pressure in the intervention group obtained a p value = 0.046 (p<, 0.05), in the control group a p value = 0.221 (p>, 0.05). Diastolic blood pressure in the intervention group obtained p = 0.024 (p <, 0.05), and in the control group diastolic blood pressure obtained p = 0.588 (p>, 0.005). This shows that there is a significant difference in systolic and diastolic blood pressure between the intervention group and the control group. Conslusion: There was a significant difference in systolic and diastolic blood pressure between the intervention group and the control group.